2020
DOI: 10.1093/cid/ciaa961
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity and Pharmacokinetics of the Hepatitis B Virus (HBV) Capsid Assembly Modulator GLS4 in Patients With Chronic HBV Infection

Abstract: Abstract Background GLS4 is a first-in-class hepatitis B virus (HBV) capsid assembly modulator (class I) that can inhibit HBV replication by interfering with the assembly and disassembly of HBV nucleocapsid. Here, we evaluated its antiviral activity, pharmacokinetics (PK), and tolerability in a double-blind, randomized, parallel, entecavir-controlled study. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 27 publications
2
28
1
Order By: Relevance
“…Acute or delayed anaphylactic reactions did not occur in the ADA-positive participants, indicating the absence of product-specific immunogenicity. Although there were no confirmed immunogenic effects of tocilizumab on drug safety and PK in this and earlier studies, we suggest closer examination of the immunogenicity and efficacies of BAT1806 and Actemra in a further phase III study involving a larger population, multiple doses, and a longer study duration because of the availability of increasingly sensitive assay methods for ADA and NAb ( Cohen et al, 2018 ; Gorovits et al, 2018 ; Zhang et al, 2020 ). The safety and tolerability of BAT1806 and the reference biosimilars RoActemra-EU and Actemra-US were observed in this study; all AEs were found to be mild to moderate in severity, with no reported SAEs, demonstrating that these products were well tolerated ( Boyce et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 63%
“…Acute or delayed anaphylactic reactions did not occur in the ADA-positive participants, indicating the absence of product-specific immunogenicity. Although there were no confirmed immunogenic effects of tocilizumab on drug safety and PK in this and earlier studies, we suggest closer examination of the immunogenicity and efficacies of BAT1806 and Actemra in a further phase III study involving a larger population, multiple doses, and a longer study duration because of the availability of increasingly sensitive assay methods for ADA and NAb ( Cohen et al, 2018 ; Gorovits et al, 2018 ; Zhang et al, 2020 ). The safety and tolerability of BAT1806 and the reference biosimilars RoActemra-EU and Actemra-US were observed in this study; all AEs were found to be mild to moderate in severity, with no reported SAEs, demonstrating that these products were well tolerated ( Boyce et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 63%
“…Overall, safety and tolerability of HOT-3010 and reference Humira ® (AbbVie) were reported in this study; all AEs were mild to moderate with no severe AEs observed, indicating good tolerance of these products (Fleischmann et al, 2019; Zhang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 55%
“…TQ-A3334 was eliminated quickly at the initial stage and slowly in the low concentration stage, resulting in a considerably slow decline in TQ-A3334 concentrations at the low concentration stage. When a longer time range for PK parameter calculation is included (e.g., extending from 0-144 h to 0-672 h), the calculated t 1/2 will be longer [20]. A longer t 1/2 and a large difference of t 1/2 were observed in this study.…”
Section: Discussionmentioning
confidence: 58%